2012
DOI: 10.1371/journal.pbio.1001428
|View full text |Cite
|
Sign up to set email alerts
|

Drosophila Interspecific Hybrids Phenocopy piRNA-Pathway Mutants

Abstract: Hybrids of two Drosophila species show transposable element derepression and piRNA pathway malfunction, revealing adaptive evolution of piRNA pathway components.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
121
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(130 citation statements)
references
References 85 publications
(153 reference statements)
6
121
3
Order By: Relevance
“…2A, 3B). Finally, the activity of endogenous clusters in D. melanogaster also seems to require a maternally inherited factor: Our analysis of previously published piRNA profiles in interspecies hybrids between D. melanogaster females and Drosophila simulans males (Kelleher et al 2012) showed that only D. melanogaster piRNA clusters generated piRNAs, while D. simulans piRNA clusters were inactive (Supplemental Fig. S12).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…2A, 3B). Finally, the activity of endogenous clusters in D. melanogaster also seems to require a maternally inherited factor: Our analysis of previously published piRNA profiles in interspecies hybrids between D. melanogaster females and Drosophila simulans males (Kelleher et al 2012) showed that only D. melanogaster piRNA clusters generated piRNAs, while D. simulans piRNA clusters were inactive (Supplemental Fig. S12).…”
Section: Discussionmentioning
confidence: 92%
“…Libraries were sequenced on the Illumina HiSeq 2000 (50-bp reads) platform. Data sets for piRNAs were extracted from available Gene Expression Omnibus (GEO) data (Kelleher et al 2012): D. melanogaster, SRX205641; D. simulans, SRX205642; and F1, SRX205643. The resulting sequencing reads were mapped against the genome using Bowtie 0.12.7 (Langmead et al 2009) with the following settings: ''-v 0-best-strata,'' retaining only uniquely mappable reads with zero mismatches.…”
Section: Chip and Chip-qpcrmentioning
confidence: 99%
“…These phenotypes, including fertility and YRV, may emerge from nongenic elements on the Y chromosome heterochromatin and may be under selection Francisco and Lemos, 2014). The piRNA pathway is a candidate to mediate Y chromosome effects in hybrids (Castillo et al, 2011;Kelleher et al, 2012) and could reconcile the low polymorphism in Y-linked protein-coding sequences (Zurovcova and Eanes, 1999;Larracuente and Clark, 2013) with YRV. Differences in the extensive blocks of heterochromatin are given by the kinds and quantities of satellite DNA and transposable elements.…”
Section: Discussionmentioning
confidence: 99%
“…At the initiation of differentiation, declining levels of Oct4 allow miR-145 to be expressed, which further suppresses Oct4 and reinforces differentiation. (Rozhkov et al 2010;Kelleher et al 2012). piRNAs are derived from distinct genomic regions called piRNA clusters, which are enriched in transposon sequences.…”
Section: Pirnas Provide Long-term Genetic Memory Of Transposon Invasionsmentioning
confidence: 99%